The implementation of M–Commerce in supply chain management system - Yousef A. Baker, El-Ebiary; Syarilla Iryani, A. Saany; Najeeb Abas, Al–Sammarraie (2019)
The progression of wireless technologies will dramatically and fundamentally transform the supply chain management, through the imminent mobile revolution. Many aspects of organizational life will be impacted by the revolution. Firstly, the crucial data will be presented in real time to help the decision makers while the ways businesses communicate, and the relationships with consumers and suppliers will dramatically change, all of which, will transform how the supply chain is managed. Issues related to the integration of Mobile Commerce (M– Commerce) and Supply Chain Management (SCM) including the dearth of killer applications, mobile device limits, networking issues, infrastructure restrictions, security matters, and user distrust in mobile applications, are examined in this paper. There are also highlights on issues including usability, user interfaces, mobile access to databases, agent technologies, and models of mobile business.